The Significant Role of Sukuk in The Indonesian Economy: A Reflection on Economic Recovery During The Covid-19 Attack - Sobar M. Johari; Dwarama Dhandya Islami (Immortalis Journal of Interdisciplinary Studies, 2026)
The COVID-19 pandemic, which has gripped the world since early 2020, has placed significant pressure on global economic activity, including Indonesia. Declining household consumption, weakening investment, and disrupted production activities have led to a significant economic contraction. In this situation, the government and the financial sector are required to provide financing instruments capable of supporting economic stability and accelerating the recovery process. One instrument that has received significant attention is sukuk. This study aims to analyze the role of sukuk in supporting the Indonesian economy by providing a specific reflection on the economic recovery period during the COVID-19 pandemic. This study uses a quantitative approach using the Autoregressive Distributed Lag (ARDL) method using quarterly data from 2011–2021, covering corporate sukuk, inflation, exchange rates, and Gross Domestic Product (GDP). The research results show that corporate sukuk significantly impacts short-term economic growth, particularly through the sukuk value in the previous period. Conversely, inflation and the exchange rate do not significantly influence either the short or long term. These findings indicate that sukuk play a strategic role as a financing instrument capable of supporting economic activity during times of crisis and is a crucial pillar in the national economic recovery process during the Covid-19 pandemic. This research strengthens the argument that sukuk market development needs to be continuously encouraged as part of Indonesia's sustainable economic development strategy.